2017
DOI: 10.1371/journal.pone.0180615
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic impact of dietary vitamin D supplementation for preventing right ventricular remodeling and improving survival in pulmonary hypertension

Abstract: BackgroundPulmonary hypertension (PH), caused by elevated pulmonary vascular resistance, leads to right heart failure and ultimately death. Vitamin D deficiency can predispose individuals to hypertension and left ventricular dysfunction; however, it remains unknown how serum vitamin D level is related to PH and right ventricular (RV) dysfunction.MethodsSerum 25-hydroxyvitamin D [25(OH)D] levels were assessed in PH patients for an association with disease severity. To examine whether vitamin D supplementation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 22 publications
(31 reference statements)
1
44
0
Order By: Relevance
“…Preliminary epidemiological studies suggested that vitD deficiency is more prevalent in PAH than in the general population. In fact, in our PAH cohort (n = 67), severe vitD deficiency was very common (median 7.17 ng/mL), in concordance with previous reports in small series (n = 22, 19, and 12) [23,24,26]. Values were very similar for idiopathic (class 1.1) and heritable PAH (class 1.2), and the sample of the drug-induced PAH (class 1.3) was too small to draw any conclusion.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Preliminary epidemiological studies suggested that vitD deficiency is more prevalent in PAH than in the general population. In fact, in our PAH cohort (n = 67), severe vitD deficiency was very common (median 7.17 ng/mL), in concordance with previous reports in small series (n = 22, 19, and 12) [23,24,26]. Values were very similar for idiopathic (class 1.1) and heritable PAH (class 1.2), and the sample of the drug-induced PAH (class 1.3) was too small to draw any conclusion.…”
Section: Discussionsupporting
confidence: 92%
“…Tanaka et al (23) also reported that total 25(OH)vitD levels negatively correlated with mPAP assessed by right-heart catheterization, with a significant positive correlation with cardiac output. According to the ESC/ERS guidelines for the diagnosis and treatment of PH and the World Health Organization [4], there are several factors that provide prognostic information and may be used to guide therapeutic decisions.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…To clarify whether vitamin D levels could be involved in PAH progression, Tanaka et al treated PAH rats with a diet containing 10;000 UI/kg of cholecalciferol [59]. Notably, in this study, they found that vitamin D supplementation in PAH rats improved survival and attenuated some typical features in PAH such as right ventricle remodeling, assessed by Fulton index (ratio of right ventricle weight to left ventricle plus septum weight), and medial thickness of muscular pulmonary arteries.…”
Section: Vitamin Dmentioning
confidence: 61%
“…Notably, in this study, they found that vitamin D supplementation in PAH rats improved survival and attenuated some typical features in PAH such as right ventricle remodeling, assessed by Fulton index (ratio of right ventricle weight to left ventricle plus septum weight), and medial thickness of muscular pulmonary arteries. Despite these benefits of vitamin D, cholecalciferol treatment did not decrease pulmonary artery pressure [59]. Moreover, in an in vitro setup, calcitriol treatment inhibited the hypoxia-induced proliferation and migration in rat pulmonary artery endothelial cells (PAEC) via miR-204/TGFβ/Smad signaling pathway.…”
Section: Vitamin Dmentioning
confidence: 99%